2005
DOI: 10.1073/pnas.0502287102
|View full text |Cite
|
Sign up to set email alerts
|

In vivo fragmentation of heparan sulfate by heparanase overexpression renders mice resistant to amyloid protein A amyloidosis

Abstract: Amyloid diseases encompass >20 medical disorders that include amyloid protein A (AA) amyloidosis, Alzheimer's disease, and type 2 diabetes. A common feature of these conditions is the selective organ deposition of disease-specific fibrillar proteins, along with the sulfated glycosaminoglycan, heparan sulfate. We have generated transgenic mice that overexpress human heparanase and have tested their susceptibility to amyloid induction. Drastic shortening of heparan sulfate chains was observed in heparanaseoverpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
116
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 29 publications
5
116
1
2
Order By: Relevance
“…Several lines of evidence have demonstrated that the disease progression is dependent on HS. We have previously found that transgenic mice overexpressing human heparanase, an HS-degrading enzyme, were resistant to experimental induction of AA amyloidosis (11), demonstrating a decisive role for HS in the pathogenic process. The present study aimed to get further insight on the molecular mechanisms of the HS and SAA interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have demonstrated that the disease progression is dependent on HS. We have previously found that transgenic mice overexpressing human heparanase, an HS-degrading enzyme, were resistant to experimental induction of AA amyloidosis (11), demonstrating a decisive role for HS in the pathogenic process. The present study aimed to get further insight on the molecular mechanisms of the HS and SAA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we have previously demonstrated that a transgenic mouse overexpressing heparanase, an HS-degrading enzyme, is resistant to experimental induction of AA amyloid (11). The overexpression of heparanase resulted in a drastic shortening of the HS chain length, demonstrating a decisive role for the polysaccharide chain length in SAA aggregation.…”
mentioning
confidence: 99%
“…Indeed, previous studies have suggested a role for heparanase in various pathophysiological conditions, including tumor metastasis (Escobar Galvis et al, 2007;Vlodavsky and Friedmann, 2001), experimental autoimmune disease (Lider et al, 1989), amyloidosis (Li et al, 2005) and delayed type hypersensitivity (DTH) reactions . A role for heparanase in tumour metastasis is supported by the strong correlation between levels of heparanase expression and metastatic potential of B16 melanoma (Vlodavsky et al, 1999) and T lymphoma (Goldshmidt et al, 2002b) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise role of HS in the pathology of amyloidosis remains unresolved, accumulating evidence suggests that HS plays an important part in amyloid deposition. Previously, we have demonstrated that amyloid A amyloidosis is correlated with HS chain length in a mouse model (15).…”
mentioning
confidence: 99%